Learning Transformation: Increasing Student Achievement through Discovery Learning - Azizah, Imro'atul; Mardiana, Dina (Dirasah International Journal of Islamic Studies, 2024)
This research aims to improve student learning outcomes by applying strategies of Discovery learning in class IX-E students at SMP Muhammadiyah 8 Batu. Based on Bruner's theory, this research uses a qualitative approach with Classroom Action Research (CAR) types. Data was collected using observation techniques, documentation, and learning results tests from informants of 30 class IX-E students at SMP Muhammadiyah 8 Batu. This CAR was carried out in two cycles, each consisting of planning, implementation, observation, and reflection stages. The research results show that the implementation of the Discovery learning strategy in the material on "understanding the postulates of naqli and the wisdom of believing in the akhirat" by students of Class IX-E of SMP Muhammadiyah 8 Batu showed positive results with indicators: (1). Result of the average class score increased to 85, with the percentage of students achieving Minimum Completeness Criteria (MCC) of 90%; (2). Students' enthusiasm and motivation in learning increased, as seen from active participation in discussion activities; (3). The Discovery learning strategy has proven effective in helping students discover the concept of iman independently and understand it better. Therefore, it is recommended that the application of this strategy be further developed in learning PAI subjects at SMP Muhammadiyah 8 Batu.